2017
DOI: 10.1017/s0144686x17001234
|View full text |Cite
|
Sign up to set email alerts
|

Generational (dis)agreements – family support, national law and older immigrants in extended households

Abstract: As detailed knowledge on multigenerational migrant families is sparse, this paper draws on quantitative and qualitative data to investigate intergenerational co-residence for older Turkish immigrants in Denmark. Registry data show that 23 per cent of Turkish immigrants in the 65–74 years age group live in intergenerational households – a level halfway between levels in Denmark and Turkey. These extended households are predominantly of the ‘culturally ideal’ type – formed by sons, sons’ wives and often the coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…married son (Aytaç, 1998). Eight per cent of the 65-to-74-year-old immigrants from Turkey live in such family arrangements, which are almost non-existent in the Danish majority (Liversage, 2019). When Sevgi moved, however, the new municipality re-evaluated the Section-94 arrangement, and reduced Damla's weekly working hours from 25 hours to just 10 hours.…”
Section: A Daughter-in-law Caring For Her Mother-in-lawmentioning
confidence: 99%
“…married son (Aytaç, 1998). Eight per cent of the 65-to-74-year-old immigrants from Turkey live in such family arrangements, which are almost non-existent in the Danish majority (Liversage, 2019). When Sevgi moved, however, the new municipality re-evaluated the Section-94 arrangement, and reduced Damla's weekly working hours from 25 hours to just 10 hours.…”
Section: A Daughter-in-law Caring For Her Mother-in-lawmentioning
confidence: 99%
“…The authors point especially towards a life course perspective to understand the inequality, urging states to consider bolstering integration policies to increase opportunities for immigrants to integrate into host-societies. Later research draws the life-course perspective further, claiming that such economic vulnerability along with nostalgic feelings towards Turkish culture later enforces the pattern of cohabitancy and intergenerational living arrangements that are more common within the group (Liversage 2019). Using Bourdieu's terms (Bourdieu and Thompson 1991), differences in immaterial (e.g.…”
Section: Theorymentioning
confidence: 99%
“…Migrating for offspring refers to some seniors for whom the main reason for migration was for caring for the younger generations, indicating the intergenerational relationship [ 4 ]. Evidence showed that the seniors that migrated for offspring have more intergenerational interactions than those separated from their children, giving more advice to their children and also receiving the support and comfort from the family in return [ 17 , 18 ]. Thus, we propose the hypothesis:…”
Section: Theoretical Backgrounds and Hypothesis Developmentmentioning
confidence: 99%